Identification of patterns of wife abuse - Follingstad, D. R.; Laughlin, J. E.; Polek, D. S.; Rutledge, L. L.; Hause, E. S. (Journal of interpersonal violence, 1991)
Typologies of 234 battered women were identified through cluster analysis to determine if a broader sample would appear similar to Snyder and Fruchtman's (1981) cluster analysis of battered women at a shelter. In addition, other variables related to wife abuse were included and new clusters were identified. Data was collected via a structured interview. Similarities with Snyder and Fruchtman's typologies suggested that certain factors may affect all battered women and are more important for investigation than the source by which the women are identified. However, the new clusters revealed a more complex picture with implications for treatment and identification